2013
DOI: 10.3844/ajisp.2013.43.47
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Driven Clinical Trials of Transfer Point Glucan #300 in Children With Chronic Respiratory Problems: Antibody Production

Abstract: The role of glucan in stimulation of immune reactions has been well-established. In this report, we focused on the antibody production in glucan-supplemented children with chronic respiratory problems. We measured the levels of salivary IgA, IgM and IgG in 40 children aged 8-12 years and evaluated the effects of 100 mg d-1 oral dose of glucan. We found a significant increase in production of all tested antibodies in the glucan-stimulated group, but a decrease of antibody production in the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…20% of the original level). It was found that the climatotherapy treatment together with speleotherapy, higher physical activity and improved nutrition resulted in significant medical improvements (Vetvicka et al, 2013a;2013b;2013c;Ostojic et al, 2013). As confirmed by other authors (Schuh, 1993), we showed that this improved regime leads to significant improvements of immune functions, lowering of the risk of infections and improvements in the state of current diseases such as respiratory problems or asthma bronchiale (Buka et al, 2006;Davis et al, 2004).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…20% of the original level). It was found that the climatotherapy treatment together with speleotherapy, higher physical activity and improved nutrition resulted in significant medical improvements (Vetvicka et al, 2013a;2013b;2013c;Ostojic et al, 2013). As confirmed by other authors (Schuh, 1993), we showed that this improved regime leads to significant improvements of immune functions, lowering of the risk of infections and improvements in the state of current diseases such as respiratory problems or asthma bronchiale (Buka et al, 2006;Davis et al, 2004).…”
Section: Introductionsupporting
confidence: 71%
“…Nutritional intervention in the form of food supplementation, with nucleotides, micronutrients, bovine colostrum or glucans, in groups with increased physical challenge have become the main research approach of numerous laboratories (Ostojic et al, 2013;Davis et al, 2004;Gunzer et al, 2012;Ostojic and Obrenovic, 2012;Riera et al, 2013;Stier et al, 2014;Wolvers et al, 2006). It is the results of our quest for an increase of immune reactions not only in athletes, but also in clinical medicine (Ciacio et al, 2014) and in possible renovation of damaged mucosal immunity in children exposed to effects of environmental contaminants (Richter et al, 2014;Vetvicka et al, 2013a;2013b;2013c). Based on these trials, several commercial supplements appeared on the market, including Oral Impal from Nestle (Ciacio et al, 2014; Sublingual nucleotides, extract from germinated barley (Ostojic and Obrenovic, 2012) or Immunoactive from Bioiberica Spain (Wolvers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Glucan supplementation can influence the levels of IgG, interferon gamma and other hematological parameters [34] . In clinical trials, short term glucan supplementation strongly influenced levels of secretory immunoglobulins [11] . In our study, 200 mg/day did not change total levels of individual groups of immunoglobulins, but caused significant changes in levels of IgG1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on excellent results in supplementing the diet with β-glucan [2,11,12] we decided to evaluate the effects of short term supplementation with β-glucan. β-Glucan is part of the group of biologically active materials and consists of highly conserved structural components of cell wall of yeast, mushroom and seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…They range from stimulation of all facets of immunity, including anti-infectious immunity, to potentiation of cancer defense, and from stress reduction to reduction of cholesterol (for review see [2,3]). The palliative effects of oral administration of yeast-derived β-glucan were recently demonstrated in clinical trials evaluating children with chronic respiratory problems [4,5].…”
Section: Introductionmentioning
confidence: 99%